Predominant Yeasts During Artisanal Mezcal Fermentation and Their Capacity to Ferment Maguey Juice - Nolasco-Cancino, Hipócrates; Santiago-Urbina, Jorge A.; Wacher, Carmen; Ruíz-Terán, Francisco (Frontiers in Microbiology, 2018)
Artisanal mezcal is produced by natural fermentation of maguey juice, which frequently results in stuck or sluggish process. Using selected indigenous starter inoculums of Saccharomyces and non-Saccharomyces yeasts is considered to be beneficial to overcome these problems preserving the essence of the artisanal process. In this work, three hundred and four yeast isolates were recovered from 17 distilleries and then grouped by ARDRA analysis, their restriction profiles were clustered in 15 groups. Four of them included 90% of all isolates, and only they were identified using the sequence of the D1/D2 domain of the large-subunit rDNA. Pichia kudriavzevii, Pichia manshurica, Saccharomyces cerevisiae and Kluyveromyces marxianus were detected as predominant species. Both species belonging to the Pichia genus were detected in 88% of the distilleries, followed by S. cerevisiae (70%) and K. marxianus (50%). In order to evaluate the fermentative capacity, one strain of each species was assessed in pure and mixed culture in two culture media, filtered maguey juice (MJ) and maguey juice including its bagasse (MJB). Findings demonstrated that non-Saccharomyces yeast presented better growth than that of S. cerevisiae. K. marxianus PA16 was more efficient for ethanol production than S. cerevisiae DI14. It produced 32 g/L of ethanol with a yield of 0.47 g/g and efficient of 90%. While, P. kudriavzevii produced more ethyl acetate (280 mg/L) than the others species. All fermentations were characterized by the presence of isobutyl and isoamyl alcohol. The presence of K. marxianus in mixed culture improved the ethanol production and volatile compounds increased using co-cultures.